2012
DOI: 10.1111/j.1574-695x.2012.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm and planktonicEnterococcus faecaliselicit different responses from host phagocytesin vitro

Abstract: Enterococcus faecalis is a commensal organism of the gastrointestinal tract but can also cause serious opportunistic infections. In addition to high levels of antibiotic resistance, the ability to form biofilms on abiotic surfaces and on in-dwelling devices within the host, complicate treatment strategies and successful outcomes of antibiotic therapy. Despite rapid advances made in recent years in understanding the genomics and virulence of this organism, much remains to be learned regarding the host response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 54 publications
1
37
1
3
Order By: Relevance
“…hominissuis, which usually downregulates TNF-␣ production during successful infection (20)(21)(22)(23)(24). Our current data with mycobacteria contrast with findings obtained in systems using Gram-positive and Gram-negative bacteria that have concluded thus far that biofilms suppress a proinflammatory response (13,14).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…hominissuis, which usually downregulates TNF-␣ production during successful infection (20)(21)(22)(23)(24). Our current data with mycobacteria contrast with findings obtained in systems using Gram-positive and Gram-negative bacteria that have concluded thus far that biofilms suppress a proinflammatory response (13,14).…”
Section: Discussioncontrasting
confidence: 56%
“…More recently, it was found that S. aureus biofilms attenuate a proinflammatory macrophage response in vivo, which could potentially explain the persistence of the biofilms in immunocompetent hosts (13). Recent work with Enterococcus faecalis has also evidenced a diminished proinflammatory response in both macrophages and dendritic cells upon contact with biofilms, in contrast to exposure to planktonic cells (14), further supporting the idea that some biofilms may circumvent or camouflage bacteria from the traditional proinflammatory innate immune response.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…As shown by previous studies, cytokines induced during infection can stimulate PI3K/Akt activation (30). Enterococcal infection can induce the robust production of proinflammatory cytokines and chemokines from macrophages (9,53). However, culture medium from E. faecalis-infected macrophages did not inhibit host cell apoptosis induced by proapoptotic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is required to distinguish these possibilities. Biofilms have been shown to be susceptible in vitro to neutrophil killing, (50,51), so it will be of interest in future experiments to define the role of biofilm formation in this model.…”
Section: Discussionmentioning
confidence: 99%